A direct comparison of porcine (Strattice™) and bovine (Surgimend™) acellular dermal matrices in implant-based immediate breast reconstruction. Issue 8 (August 2017) - Ball, Jessica F.; Sheena, Yezen; Tarek Saleh, Dina M.; Forouhi, Parto; Benyon, Sarah L.; Irwin, Michael S.; Malata, Charles M.
Summary: Introduction: Acellular dermal matrix (ADM) assisted implant-based breast reconstruction (IBBR) has grown in popularity over traditional submuscular techniques. Numerous human, bovine or porcine derived ADMs are available with the type used varying considerably worldwide. Yet, comparative evidence for the efficacy of different ADMs particularly xenogenic is limited. This study directly compares early outcomes of porcine (Strattice™) and bovine (Surgimend™) ADMs in IBBR. Method: Retrospective study of sequential experience of immediate IBBR using Strattice or Surgimend ADM. Data was collected for patients undergoing ADM assisted IBBR after prophylactic or therapeutic mastectomy in Cambridge (October 2011–March 2016). Patient demographics, adjuvant and neoadjuvant therapies, operative details, postoperative management and outcomes were analysed. Key results: Total of 81 patients underwent IBBR with ADM; 38 bilateral and 43 unilateral (n = 119 breasts). Strattice was used in 30 breasts (25%) and Surgimend in 89 (75%). Analysis of patient specific variables showed statistical significance only for higher mastectomy weight in the Strattice group (367.1 ± 159.3 g versus 296.3 ± 133.4 g; P = 0.0379). Strattice was associated with higher rates of skin erythema post-operatively (16.7% versus 4.5%; P = 0.044). Analysed per woman or per breast, there was no statistically significant difference in rates of haematoma, infection, wound dehiscence, skin necrosis or seroma, although there was a trend towards more complications with Strattice. Conclusion: This study found significantly higher rates of skin erythema and a trend towards higher complication rates with Strattice in IBBR. Randomised controlled trials comparing different ADM outcomes are needed to inform best practice.